Assessing the investigative needs of rural law enforcement - Gilbert, James N. (American journal of criminal justice, 1984)
Although the topic of rural crime has received relatively little attention in traditional criminal justice research, the more specialized subtopic of rural criminal investigation has received even less. As criminological research and public attention begin to focus upon rural crime due to its rapid growth, rural police agencies will need to assess their investigative attitudes and resources in an effort to reduce accelerating crime rates. This paper surveyed the attitudes of 52 rural sheriffs in an effort to gather information necessary to assess needs and attitudes unique to the rural investigation.